Parameter analysis for speed skating performance - van der Kruk, E. (Delft University of Technology, 2018)
Speed skating is a rather special form of locomotion. While in most types of human locomotion, humans generate forces by pushing against the environment in the opposite direction of motion, in speed skating the skater pushes sideward to propel himself forward; Insight in the details of the technique can help a speed skater improve his performance. Therefore we would like to develop an optimal measurement system to collect real-time accurate kinetic data of a speed skater. These data will be used to give real-time feedback to the skater and his coach. Additionally the data will be used for the development of a 3D biomechanical model that can simulate the motion of a speed skater and eventually can be used for skating technique optimization.